2011
DOI: 10.1007/s10157-011-0567-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of chronic kidney disease mass screening test in Japan

Abstract: BackgroundChronic kidney disease (CKD) is a significant public health problem. Strategy for its early detection is still controversial. This study aims to assess the cost-effectiveness of population strategy, i.e. mass screening, and Japan’s health checkup reform.MethodsCost-effectiveness analysis was carried out to compare test modalities in the context of reforming Japan’s mandatory annual health checkup for adults. A decision tree and Markov model with societal perspective were constructed to compare dipsti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 39 publications
2
50
0
1
Order By: Relevance
“…74 Systematic population-based CKD screening should be considered by societies around the world to determine the portion of the population at risk versus those affected by CKD. [75][76][77] Currently, few societies implement systematic screening for adults unless they have risk factors, such as diabetes mellitus or advanced age. 78 Considering that early-to moderate stage CKD is relatively asymptomatic, screening has multiple advantages.…”
Section: Population-level Ckd Screeningmentioning
confidence: 99%
“…74 Systematic population-based CKD screening should be considered by societies around the world to determine the portion of the population at risk versus those affected by CKD. [75][76][77] Currently, few societies implement systematic screening for adults unless they have risk factors, such as diabetes mellitus or advanced age. 78 Considering that early-to moderate stage CKD is relatively asymptomatic, screening has multiple advantages.…”
Section: Population-level Ckd Screeningmentioning
confidence: 99%
“…Other studies combine eGFR evaluation with microalbuminuria and/or proteinuria [11,12,13,14]. However, there is some debate whether these full tests are economically viable on a large scale [7,9,15]. CKD screening may be cost effective only in high-risk populations or general populations that have a high prevalence of CKD; otherwise simpler testing might be needed to reduce costs [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Results of previous studies showed that use of dipstick urinalysis to detect proteinuria but was inadequate in the routine screening for the detection of early stage CKD due to insufficient sensitivity and specificity (6). In the general population, screening combined with serum concentrations of creatinine or other biomarkers is therefore likely to be appropriate and cost-effective for the stratification of high-risk individuals (7). Identification of genetic variants that confer susceptibility to CKD may thus be important in determining which patients are recommended for frequent checkup.…”
Section: Introductionmentioning
confidence: 99%